Pendidikan Tauhid dalam Surah Al-Ikhlash Prespektif Ibnu Katsir - Afrudin Afrudin; Abdul Hadi; Muhammad Hambal Shafwan (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
This research explains how the Education of Tawheed in Surah Al-Ikhlas from the perspective of Ibn Kathir in the Book of Tafsir al-Qur'an al-'Azim. The research method employed in this study is literature review. This study analyzes and discusses the values of Tawheed education found in Surah Al-Ikhlas and how these values are relevant to the contemporary educational context. The results of this study can conclude that in Surah Al-Ikhlas, there is a strong foundational concept in Tawheed education, as it contains explanations about the oneness of Allah SWT, His attributes, and the rejection of worshiping other than Him.